Change of Cr concentration from past to present in areas with elevated air pollution - Koc, I.; Cobanoglu, H.; Canturk, U.; Key, K.; Kulac, S.; Sevik, H. (Springer Science and Business Media LLC, 2023)
Chromium (Cr) is one of the most detrimental heavy metals, the concentration of which has increased significantly in nature in the last century. Cr pollution can cause toxic and harmful health effects by causing high accumulation levels in animal and human tissues, seriously affecting ecosystems and natural resources. Due to environmental and human health risks, it is critical to track the change of Cr pollution in the air and reduce it. This study aims to determine the suitable tree species that can be used for observing and reducing Cr pollution. For this purpose, samples (wood, inner bark and outer bark) taken from Pinus pinaster, Cupressus arizonica, Picea orientalis, Cedrus atlantica, and Pseudotsuga menziesii species grown in Duzce, Turkiye, which is among the 5 most polluted cities in Europe according to the World Air Pollution 2021 Report, were examined. The accumulation of Cr concentration was determined by species (40-year-old), organ, and direction, and changes in age range were evaluated. As a result of the study, while the highest concentration levels were determined in the outer bark in general, it was interpreted that the branching structure affected this situation. The study results reveal that, in general, Cr pollution is mainly caused by traffic. It has been determined that C. arizonica and P. menziesii are the suitable tree species that can be used for observing and reducing Cr pollution in the air.
Keywords: Chromium; China; Heavy metal; Speciation; Air pollution; Cupressus arizonica; Plants; Detoxification; Elements; Pseudotsuga menziesii; Chromium Toxicity